Lg(cos^2014 x) = lg(sin^2014 x)

Lg(cos^2014 x) = lg(sin^2014 x)
Гость
Ответ(ы) на вопрос:
Гость
 cos^2 (2014x) = sin^2 (2014 x); cos^2(2014x) - sin^2(2014x) = 0; (cos(2014x) - sin(2014x) *(cos(2014x) + sin(2014x)) = 0; 1) cos (2014x) = sin(2014x);  / cos(2014x) ≠ 0; tg(2014x) = 1; 2014 x = pi/4 + pi*k; x = pi/8416 + pik/ 2014; k ∈ Z. 2) cos(2014x) = - sin(2014x);   / cos(2014x) ≠ 0; tg(2014 x) = - 1; x = - pi/4 + pi*k;  x = - pi/8416 + pi/2014; k∈Z. Объединив 2 ответа, получим x = + - pi/8416 + pi*k / 2014; k ∈ Z
Не нашли ответ?
Ответить на вопрос
Похожие вопросы